Acute phase of COVID-19 is associated with elevated plasmablasts in the blood - Beran, Ondřej; Matúšková, Kateřina; Bartovská, Zofia; Bartoš, Oldřich; Holub, Michal (Bratislavské lekárske listy, 2022)
OBJECTIVES: The study was aimed at the characterization of humoral immunity in acute SARS-CoV-2 infection. BACKGROUND: Humoral immunity plays a central role in the protection from infection due to SARS-CoV-2, causative agent of coronavirus diseases 2019 (COVID-19). PATIENTS AND METHODS: In 24 adult patients hospitalized with COVID-19, the functional subsets of circulating B-lymphocytes and SARS-CoV-2 specific IgA and IgG antibodies were analyzed using a flow cytometry and immunoassays, respectively. RESULTS: Circulating plasmablasts and memory B-lymphocytes were significantly elevated and regulatory B-lymphocytes significantly decreased in the patients in comparison with 11 age- and sex-matched SARS-CoV-2 seronegative healthy adults. Next, circulating plasmablasts correlated negatively with the levels of SARS-CoV-2 specific IgG antibodies, which were detectable in 9 out of 15 tested patients. In addition, SARS-CoV-2 specific IgA antibodies were detectable in 13 of 15 tested patients and did not demonstrate correlation with any B-lymphocyte subset. CONCLUSION: Severe course of COVID-19 is associated with significant changes of phenotypes of circulating B-lymphocytes and elevated circulating plasmablasts correlate with decreased SARS-CoV-2-specific IgG antibodies (Tab. 2, Fig. 3, Ref. 14).
Keywords: B-lymfocyty; Aged; statistika jako téma; imunoglobulinové izotypy; lidé středního věku; senioři; lidé; Adult; Middle Aged; dospělí; B-Lymphocytes; Female; plazmatické buňky; COVID-19; Male; Statistics as Topic; ženské pohlaví; Immunoglobulin Isotypes; Humans; mužské pohlaví; Immunity, Humoral; Flow Cytometry; průtoková cytometrie; humorální imunita; Plasma Cells